Subnational inequalities in years of life lost and associations with socioeconomic factors in pre-pandemic Europe, 2009-19: an ecological study - Chen-Xu, José; Varga, Orsolya; Mahrouseh, Nour; Eikemo, Terje Andreas; Grad, Diana A; Wyper, Grant M A; Badache, Andreea; Balaj, Mirza; Charalampous, Periklis; Economou, Mary; Haagsma, Juanita A.; Haneef, Romana; et al. (My University, 2024)
Health inequalities have been associated with shorter lifespans. We aimed to investigate subnational geographical inequalities in all-cause years of life lost (YLLs) and the association between YLLs and socioeconomic factors, such as household income, risk of poverty, and educational attainment, in countries within the European Economic Area (EEA) before the COVID-19 pandemic.
Keywords: Europe; Female; Humans; Life Expectancy; Male; Pandemics; Poverty; Socioeconomic Factors